Congenital unilateral renal agenesis: Prevalence, prenatal diagnosis, associated anomalies. Data from two birth‐defect registries. Issue 15 (19th July 2017) - Laurichesse Delmas, Hélène; Kohler, Monique; Doray, Bérénice; Lémery, Didier; Francannet, Christine; Quistrebert, Jocelyn; Marie, Cécile; Perthus, Isabelle
Abstract : Background: The different mechanisms leading to a solitary kidney should be differentiated because the long‐term outcome might be different. The fetal period is the best moment to make a true diagnosis of congenital unilateral renal agenesis (URA). The objective was to determine the prevalence of URA at birth. The secondary objectives were to describe the evolution of sensitivity of prenatal diagnosis over time and the different forms of URA (isolated and associated with other malformations) detected up to 1 year. Methods: The cases were retrospectively identified through two French population‐based birth defect registries (Auvergne and Bas‐Rhin) between 1995 and 2013. Stillbirths and fetuses up to 22 weeks of gestation and infants up to 1 year old with URA were included. Results: A total of 177 cases of URA were registered. The prevalence at birth was 4.0/10, 000. The overall prenatal prevalence was 3.6/10, 000 (isolated URA: 2.8/10, 000). URA were isolated (59.9%), associated with isolated contralateral congenital anomaly of kidney or urinary tract (CAKUT) (7.3%) and with other extra‐renal anomalies (32.8%). The total proportion of contralateral CAKUT was 15%. Only three cases presented an aneuploidy, prenatally detected and conducting to a termination of pregnancy. The sensitivity of prenatal diagnosis improved over time (from 54.2% in 1995 to 1997 to 95.8% in 2010 to 2013; p = 0.002). Conclusion: Our study provides estimates of prevalence of URA at birth. A longitudinal cohort from the antenatal period to puberty should be performed to determine the prognosis of the contralateral kidney among these children with isolated, associated with contralateral CAKUT and URA with extra‐renal anomalies. Birth Defects Research 109:1204–1211, 2017. © 2017 Wiley Periodicals, Inc.